Typification of the name Dianema harveyi (Dianemataceae) - Ronikier, Anna (Phytotaxa, 2023)
Revision of available syntypes of Dianema harveyi Rex revealed that two of them represent another species, Prototrichia metallica. In order to clarify the species interpretation, Dianema harveyi is typified, described based on original material, and illustrated.